A Review on Infrared Spectroscopy of Borate Glasses with Effects of Different Additives. (14th November 2012) - Gautam, Chandkiram; Yadav, Avadhesh Kumar; Singh, Arbind Kumar
Abstract : Borate glasses are the technologically important class of glasses and play a significant role in various applications. Borate glasses contain planar BO3 groups as structural units, rather than tetrahedral SiO4 groups. The oxygen atoms are, as in SiO2, again connected to two network-forming atoms, in case of boron. The radial distribution analysis describes the B2 O3 glass structure as consisting of boroxol rings, that is, planar rings containing three boron atoms and three oxygen atoms. The network forming of the B2 O3 and the SiO4 is affected with the addition of some metal cation additives Pb, Zn, Cd, and so forth. These additives also work as a network modifier and a nucleating agent for crystallization of glass. Therefore, the optical properties of the borate glasses have been changed significantly.